Thermophysical properties of fluids from dynamic light scattering - Will, Stefan; Leipertz, Alfred (Springer Verlag (Germany), 2001)
In a continuous development for more than three decades, dynamic light scattering (DLS) has evolved into a versatile and powerful technique for the determination of transport and other thermophysical properties of fluids. The success is founded on its application in a macroscopic thermodynamic equilibrium, i.e., without the need for employing external gradients, to determine a large variety of properties, which can be derived, in some instances even simultaneously, by an appropriate experimental approach and a corresponding signal analysis. The principles, essential features, and variants of the technique are reviewed and a survey on the determination of various desired transport and thermophysical properties is given, both for the application of light scattering from hulk fluids and for the variant of surface light scattering (SLS). The stage of development and the corresponding uncertainties are discussed for the measurement of the individual quantities, and the performance of the method is demonstrated by representative experimental results for relevant fluids.
Keywords: dynamic light scattering; surface light scattering; thermophysical properties; transport coefficients